Association of dietary patterns of American adults with bone mineral density and fracture. Issue 13 (21st May 2018) - Mazidi, Mohsen; Kengne, Andre Pascal; Vatanparast, Hassan
Abstract: Objective: In a representative sample of US adults, we investigated the associations of nutrient patterns (NP) with bone mineral density (BMD) and fractures. Design: Cross-sectional. Setting: US community-based National Health and Nutrition Examination Survey (NHANES). Subjects: Participants with measured data on dietary intake and BMD from 2005 to 2010 were included. Principal components analysis was used to identify NP. BMD was measured using dual-energy X-ray absorptiometry. ANCOVA, adjusted logistic and linear regression models were employed, accounting for the complex survey design and sample weights. Results: We included a total of 18 318 participants, with 47·0 % ( n 8607) being men. The mean age was 45·8 years with no sex difference. Three NP emerged, explaining 55·9 % of the variance in nutrient consumption. Multivariable-adjusted linear regressions revealed significant inverse associations between the 'high-energy' NP (rich in carbohydrates and sugar, total fat and saturated fat) and total femur, femoral neck, trochanter and intertrochanter BMD ( β coefficient: −0·029, −0·025, −0·034 and −0·021, respectively, all P <0·001), while there were significant associations between the 'nutrient-dense' NP (rich in vitamins, minerals and fibre) and 'healthy fat' NP (high dietary PUFA and MUFA) and BMD at total femur, femoral neck, trochanter and intertrochanter (all P <0·001). In adjusted logistic regression models, the odds of hip, wrist or spine fractures did not vary significantly across NP quartiles. Conclusions: Nutrient-dense and healthy fat NP are associated with higher BMD at various bone sites, while the high-energy NP is inversely associated with BMD measures.